f(0)=7,2 >0
f(1)=1-3,5-5+7,2=-0,3 <0
⇒
первый корень на [0;1]
Делим пополам
[0;0,5] и [0,5;1]
f(0,5)=0,5^4-3,5*0,5^3-5*0,5^2+7,2 >0⇒
корень на отрезке [0,5;1]
Снова делим пополам
[0,5;0,75] и [0,75;1]
f(0,75)=0,75^4-3,5*0,75^3-5*0,75^2+7,2 >0⇒
корень на отрезке [0,75;1]
Снова делим пополам
[0,75;0,875] и [0,875;1]
f(0,875)=0,875^4-3,5*0,875^3-5*0,875^2+7,2 >0⇒
корень на отрезке [0,875;1]
Снова делим пополам
[0,875;0,9375] и [0,9375;1]
f(0,9375)=0,9375^4-3,5*0,9375^3-5*0,9375^2+7,2 >0⇒
корень на отрезке [0,9375;1]
Снова делим пополам
[0,9375;0,96875] и [0,96875;1]
f(0,96875)=0,9375^4-3,5*0,9375^3-5*0,9375^2+7,2 >0⇒
корень на отрезке [0,96875;1]
Снова делим пополам
[0,96875;0,984375] и [0,984375;1]
f(0,984375)=0,9375^4-3,5*0,9375^3-5*0,9375^2+7,2 <0⇒
корень на отрезке [0,96875;0,984375]
x₁≈0,98
Аналогично,
f(4) <0
f(5) >0
второй корень на [4;5]
x₂≈4,5
10796 - 78*х=6740
78х = 10796-6740
78х = 4056
х=4056:78
х=52
68*х + 139007 = 995603
68х=995603-139007
68х=856 596
х=856 596:68
х=12 597
у*768-456=456504
у*768=456504+456
у*768 = 456 960
у=456 960:768
у=595
67097-567:у=67090
567:у=67097-67090
567:у=7
у=567:7
у=81
98072:х+768 = 8312
98072:у=8312-768
98072:у=7544
у=98072:7544
у=13
67809+65*х=765389
65*х=765389-67809
65*х=697 580
х=697 580:65
х=10732
94563:у-371=340
94563:у=340+371
94563:у=711
у=94563:711
у=133
(989+х)*5=324565
989+х=324565:5
989+х=64913
х=64913-989
х=63924
22982-675*х=5432
675*х=22982-5432
675*х=17550
х=17550:675
х=26
Пошаговое объяснение: